Biomarkers in ANCA associated vasculitis: clinical utility, pitfalls and their role in the outcomes assessment - Marvisi, Chiara; Ricordi, Caterina; Catellani, Cecilia; Croci, Stefania; Muratore, Francesco; Salvarani, Carlo (Frontiers in Immunology, 2025)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) are rare autoimmune diseases with multisystemic organ involvement. Their pathogenesis remains incompletely understood, and reliable biomarkers for disease activity and treatment response are lacking.This review explores current and emerging biomarkers in AAVs to identify disease phenotypes and activity, aiming to optimize management and immunosuppressive treatment. Serological, cellular, and urinary biomarkers will be discussed, focusing on their current utility in clinical practice for assessing disease activity, damage related to the disease, and prognosis. Promising biomarkers and novel methodologies for detecting future biomarkers will also be briefly discussed.